2012
DOI: 10.1179/1743281211y.0000000052
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional FEM study of fluid flow in mould for beam blank continuous casting: influence of nozzle structure and parameters on fluid flow

Abstract: The aim of this work was to analyse the influence of the nozzle structure and parameters on the molten steel flow in beam blank continuous casting. A three-dimensional steady state finite element model was developed to compute the flow field and the meniscus fluctuation in the mould. The volume of fluid model was used to track the free surface evolution at the meniscus. It can be concluded that compared with a through conduit submerged entry nozzle (SEN), a three lateral hole SEN will reduce the impact depth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 4 publications
1
11
0
5
Order By: Relevance
“…A profundidade do jato foi analisada através da observação do comportamento do jato de tinta ao longo do molde, método semelhante ao aplicado por Chen et al [5]. Lee et al [6], Yang et al [3] e CHEN et al [4,5], destacam que os fluxos recirculatórios de aço na região da alma e da ponta da flange afetam o perfil de crescimento da pele sólida do beam blank, e assim, o crescimento da pele sólida nas regiões do filete é mais lento nos estágios iniciais da solidificação.…”
Section: Profundidade Do Jatounclassified
See 1 more Smart Citation
“…A profundidade do jato foi analisada através da observação do comportamento do jato de tinta ao longo do molde, método semelhante ao aplicado por Chen et al [5]. Lee et al [6], Yang et al [3] e CHEN et al [4,5], destacam que os fluxos recirculatórios de aço na região da alma e da ponta da flange afetam o perfil de crescimento da pele sólida do beam blank, e assim, o crescimento da pele sólida nas regiões do filete é mais lento nos estágios iniciais da solidificação.…”
Section: Profundidade Do Jatounclassified
“…Lee et al [6], Yang et al [3] e CHEN et al [4,5], destacam que os fluxos recirculatórios de aço na região da alma e da ponta da flange afetam o perfil de crescimento da pele sólida do beam blank, e assim, o crescimento da pele sólida nas regiões do filete é mais lento nos estágios iniciais da solidificação. Da mesma forma, o crescimento da pele sólida nas regiões do filete e do centro da flange é retardado devido ao impingimento do fluxo de aço da válvula submersa sobre a pele sólida.…”
Section: Profundidade Do Jatounclassified
“…One of them also accounts for the use of a multi-port nozzle, up to three ports, one pointing towards the mould center and two at 120° from each other, pointing towards the mould narrow faces. 8) Nevertheless, also with this particular geometrical feature two symmetric nozzles are foreseen. Of course, the use of two nozzles, placed at centre section half-way between flange tips ('triple point'), brings about a particular lay-out arrangement to couple tundish and mould feeding, different from casters of other as-cast shapes.…”
Section: Technical Approach and Modelling Descriptionmentioning
confidence: 99%
“…Shen found that the formation of longitudinal surface cracks in the slab is related to the heat transfer and mold taper [5]. In previous studies, Chen et al developed a three-dimensional FEM to compute the flow field of molten steel in the beam blank mold and found that the most rational rake angle for the three lateral hole SEN is 9°and the SEN immersion depth is 200-250 mm when casting speed is 0.9-1.1 m·min À1 [6]. Chen et al conducted a transient thermo-mechanical FEM, analyzed the two-dimensional temperature and stress-strain fields of the solidification process in detail and search out the optimum cooling parameters [7].…”
Section: Introductionmentioning
confidence: 99%